Analisis Sistem Drainase di Kawasan Pemukiman pada SubDAS Aur Palembang (Studi Kasus : Pemukiman 9/10 Ulu) - Isfandari, Defi Tesha (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2014)
One of the area in Palembang City that often floods is 9/10 ulu residential on sub DAS Aur. Existing drainage channels have dimensions that are not sufficient to flow peak dischange caused by storm and tides. Therefore, it is necessary to study the drainage channels in the residential areas. The first stage in the analysis begins with hydrologic analysis to calculate the distribution of rainfall using maximum daily rainfall data for 20 years from 1993 to 2012. The next step calculates the design rainfall intensity, then calculate the design rainfall hyetograph using ABM method (Alternating Block Method). By using SWMM 5.0 (Storm Water Management Model 5.0) program can analyze the available drainage system in the residence, then the input data was complete. Floods simulation about the improper water drainage can be achieved after inputting the data. Redesigning the rational method and simulated by SWMM 5.0 program to replace the previous channel dimensions and dimensional data input channels planned, then the simulation results with good water flow in the channel was ideal.Key Words: Drainage system, flood, rational method, SWMM 5.0